2003
DOI: 10.1073/pnas.0737647100
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids determining enzyme-substrate specificity in prokaryotic and eukaryotic protein kinases

Abstract: The binding between a PK and its target is highly specific, despite the fact that many different PKs exhibit significant sequence and structure homology. There must be, then, specificity-determining residues (SDRs) that enable different PKs to recognize their unique substrate. Here we use and further develop a computational procedure to discover putative SDRs (PSDRs) in protein families, whereby a family of homologous proteins is split into orthologous proteins, which are assumed to have the same specificity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
86
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 43 publications
(76 reference statements)
1
86
0
Order By: Relevance
“…In most cases, these methods are based on the ideas of Mirny and Gelfand (27)(28)(29)(30), who suggested that functional specificity is determined by protein regions that are more similar within a group having a common function than between groups with distinct functions. Previous analysis of this Significance Specificity-determining positions (SDPs) account for distinctions in function across a protein family.…”
mentioning
confidence: 99%
“…In most cases, these methods are based on the ideas of Mirny and Gelfand (27)(28)(29)(30), who suggested that functional specificity is determined by protein regions that are more similar within a group having a common function than between groups with distinct functions. Previous analysis of this Significance Specificity-determining positions (SDPs) account for distinctions in function across a protein family.…”
mentioning
confidence: 99%
“…The authors used various statistical models to evaluate significance of mutual information and to identify so-called "specificity-determining" positions. [22][23][24] In our approach, we use two measures to evaluate the conservation of positions among proteins within the same subfamily and their diversity between different subfamilies. The combined two measures (entropies) result in a high resolution in identifying binding sites and other functional sites.…”
Section: Two-entropies Plot Versus "Mutual Information"mentioning
confidence: 99%
“…Thus, we are currently applying our method to the superfamily of protein kinases, which have already been analyzed by mutual information. 22 …”
Section: Two-entropies Plot Versus "Mutual Information"mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments in structural bioinformatics have contributed greatly to our understanding of protein-protein interactions (1)(2)(3)(4)(5)(6). Several groups have addressed the feasibility of computational redesign of protein-protein interactions by using native or homologous protein-protein interfaces (7)(8)(9)(10).…”
mentioning
confidence: 99%